A bilevel optimal operation model of multi energy carriers system considering part load rate and demand response. (June 2021) - Huang, Yu; Ding, Peng; Wang, Yutao; Li, Shuqin; Yang, Kai; Li, Yongling
Abstract: The demand response (DR) scheme could benefit both the supply side and demand side of multi energy carriers system (MECS) by reshaping the pricing signals. However, tremendous difficulties are introduced in designing a reasonable pricing mechanism to impart the enthusiasm for participating in the DR scheme. In this paper, an optimal operation model with high authenticity is established which is tractable after the model transformation, linearization, and relaxation techniques. Firstly, a bilevel optimal operation model considering the part load rate (PLR) characteristics of units and DR scheme under real-time pricing is developed. Secondly, Karush-Kuhn-Tucker (KKT) conditions are utilized to transform this bilevel optimization problem into a single-level optimization. Thirdly, the piecewise linearization technique is described to cope with the non-linear PLR characteristics of the units. Finally, by applying the previous approach, a MILP formulation is formed which could be solved efficiently by the commercial solver. Case studies are conducted to verify the effectiveness of the proposed model and approach and the simulation results show that the revenue of the supply side is increased by 45.20 $ and the cost of the demand side is decreased by 74.91 $ which means both sides could benefit from the DR scheme.